A bibliometric analysis of cerebral small vessel disease - Yan, Xiaoxiao; Zhang, Yongyin; He, Ruqian; Chen, Xiachan; Lin, Mian (Frontiers in Aging Neuroscience, 2024)
Background: Cerebral small vessel disease (CSVD) is a significant contributor to both stroke and dementia. While numerous studies on CSVD have been published, herein, we have conducted a bibliometric examination of the literature on CSVD, revealing its hot spots and emerging patterns.We used the Web of Science Core Collection as our primary database and conducted a literature search from January 2008 to January 2023. CiteSpace, VOSviewer, online bibliometric platform, and R-bibliometrix were employed to conduct bibliometric analysis and network visualization, including the number of publications, countries, institutions, journals, citations, authors, references, and keywords.Results: A total of 4,893 publications on CSVD were published in 790 journals by 19,066 authors at 3,862 institutions from 84 countries. The United States produced the most written works and had a significant impact in this field of study. The University of Edinburgh had the highest publication count overall. The journal with the most publications and co-citations was Stroke. Wardlaw, Joanna was the most prolific author and commonly cited in the field. The current areas of research interest revolved around "MRI segmentation" and "Enlarged perivascular spaces in the basal ganglia."We conducted a bibliometric analysis to examine the advancements, focal points, and cutting-edge areas in the field of CSVD to reveal potential future research opportunities. Research on CSVD is currently rapidly advancing, with a consistent rise in publications on the topic since 2008.At the same time, we identified leading countries, institutions, and leading scholars in the field and analyzed journals and representative literature. Keyword co-occurrence analysis and burst graph emergence detection identified MRI segmentation and Basal ganglia enlarged perivascular spaces as the most recent areas of research interest.